2001
DOI: 10.3171/jns.2001.94.5.0822
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ophthalmic artery aneurysm

Abstract: The authors report on two patients with peripheral ophthalmic artery (OphA) aneurysms and demonstrate the mechanism by which these lesions are formed by using OphA color Doppler flow velocimetry imaging. During formation of these two aneurysms, the hemodynamic stress on the OphA was quite significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The patient was discharged from the hospital with no neurological symptoms. During the follow-up period of 1.5 years there were no neurological symptoms, including loss of visual acuity and exophthalmos [12] . Those dAVFs with cortical venous drainage have been identifi ed as lesions with the highest propensity to manifest aggressive clinical symptoms, mandating prompt therapy [3] .…”
Section: Discussion ▼mentioning
confidence: 89%
“…The patient was discharged from the hospital with no neurological symptoms. During the follow-up period of 1.5 years there were no neurological symptoms, including loss of visual acuity and exophthalmos [12] . Those dAVFs with cortical venous drainage have been identifi ed as lesions with the highest propensity to manifest aggressive clinical symptoms, mandating prompt therapy [3] .…”
Section: Discussion ▼mentioning
confidence: 89%
“…The high velocity in the ophthalmic artery was suggested as the cause of hemodynamic stress leading to development of aneurysms at this location 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Ophthalmic artery aneurysms that cause visual symptoms are usually located in the intracanalicular segment because of the close proximity and limited space available 11 12. Kawaguchi et al 3 reported two cases of ophthalmic artery aneurysm, one of which was associated with dural AVF while the second was associated with Moya Moya disease. One aneurysm was treated with clipping.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical clipping, parent vessel occlusion and trapping–resection while saving the central retinal artery are all described as possibilities 1–3 9. Kawaguchi et al 3 in their two-patient case series performed clipping on one of the aneurysms. Ogawa et al 9 described a case of symptomatic ophthalmic artery aneurysm that was treated with clipping/resection of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation